2020
DOI: 10.3390/app10238312
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Arthroscopic Microfracturation of Knee Chondral Defects in Osteoarthritis

Abstract: Purpose: The purpose of this study was to estimate the effect of platelet-rich plasma (PRP) augmentation in microfractures of chondral lesions in elderly individuals. Methods: 29 patients with knee osteoarthritis were enrolled in the single-blinded randomized study. The study group consisted of 16 patients and 13 were in the control group. All surgeries were performed in the same manner. The PRP injection was made in a dry arthroscopy directly over the microfractures. The evaluation was performed preoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…The study showed an improvement in OA symptoms with a bone marrow derived cultured stem cell injection; the VAS score was found improved even at 2 years post treatment. However, the authors pointed out that there were no studies comparing the effect of BMAC and culture expanded bone marrow derived mesenchymal stem cells (BM-MSCs) [31].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed an improvement in OA symptoms with a bone marrow derived cultured stem cell injection; the VAS score was found improved even at 2 years post treatment. However, the authors pointed out that there were no studies comparing the effect of BMAC and culture expanded bone marrow derived mesenchymal stem cells (BM-MSCs) [31].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritic changes were also apparent in active duty soldiers younger than 20 years of age [ 9 ]. In the early stages of the disease, there were multiple methods of treatment including surgical and conservative treatment [ 10 , 11 , 12 , 13 ]. Nevertheless, at the end stage of the disease, total knee arthroplasty (TKA) is the gold standard of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods of treatment, including conservative and surgical measures have been proposed for the treatment of OA [ 11 , 12 , 13 , 14 ]. The end stage disease is indicated for arthroplasty.…”
Section: Introductionmentioning
confidence: 99%